THE DECORATION FORM OF CERAMIC REVOLVING CORE BOTTLES IN THE QING DYNASTY - Liying, Li; Wan Jamarul Imran, Wan Abdullah Thani (UNIMAS Publisher, 2022)
The ceramic revolving core bottle(CRCB) is one of the most important ceramic art varieties in the Qing Dynasty. It has an entirely different form characteristic from other Chinese ceramic varieties. This paper uses the formal analysis method to analyse theformal language features of Qing Dynasty CRCB by comparing them with other Chinese ceramic varieties, such as the differences in colour, decorative composition and structure between them and different ceramic types. The analysis shows that the Qing Dynasty CRCB has great particularity in form, such as the use of more abundant colours. Decorative painting tends to adopt the form of long scroll painting. Ceramic decoration pays attention to the expression of stereo feeling on the structure. The formation of these formal characteristics is closely related to the ruler's control over ceramic production. It benefited from applying Chinese classical garden art forms in ceramics and the revival of traditional Chinese classical painting. Through the study of the CRCB form, it is helpful to connect ceramic art research with other Chinese art forms through the characteristics of CRCB in form, and analysethe relationship between them, expand the perspective of traditional research, and promote the application of interdisciplinary research in ceramic research.